Accessibility Measures for Analyses of Land-Use and Travelling with Geographical Information Systems - Makr´í, Maria-Christina; Folkesson, Carolin (Proceedings from the Annual Transport Conference at Aalborg University, 1999)
This paper compares existing accessibility measures and develops and varies some of these measures for comprehensive analysis of land-use impact on accessibility and on travelling patterns using GIS. The paper is based on a literature survey, a review of the geographical information in digital maps and available data on population and potential destinations. The focus is on place accessibility, but it also touches on individual accessibility. The accessibility measure chosen for the first case study is a zone-to-point distance measure, estimated separately for different types of opportunities and different road-users. The distances between origins and destinations are measured as the shortest network distance and actual driving time. A customised ArcView Network Analyst is used. Integral zon-to- zon place accessibility measures are chosen for the second case study. The main part of the calculations will be conducted in programs suitable for matrix operations and for database analyses, and the output will be processed in digital maps for presentation.